Multistage ore-forming processes and metal source recorded in texture and composition of pyrite from the Late Triassic Asiha gold deposit, Eastern Kunlun Orogenic Belt, western China. (15th October 2021) - Liang, Gai-Zhong; Yang, Kui-Feng; Sun, Wei-Qiang; Fan, Hong-Rui; Li, Xing-Hui; Lan, Ting-Guang; Hu, Huan-Long; Chen, You-Wei
Graphical abstract: Highlights: Hydrothermal monazite of the Asiha gold deposit has a U-Pb age of ca.227 Ma. Four generations of ore-related pyrite have been identified in this deposit. The ore-forming materials were derived from felsic magma and mafic-volcanic rocks. Abstract: The Asiha vein-type gold deposit, located in the Eastern Kunlun Orogenic Belt, provides an excellent opportunity for deciphering sources of metals and origins of orogenic intrusion-related gold systems. Within this deposit, four types of pyrite have been distinguished in three stages of hydrothermal activities. Pyrite (Py1) occurs in quartz-pyrite veins (stage I); pyrite (Py2), consisting of core (Py2a) and rim (Py2b), occurs in quartz-polymetallic sulfide veins (stage II); pyrite (Py3) occurs in quartz-pyrite-chalcopyrite veins (stage III). Py1 contains high concentrations of As (median of 2090 ppm) and Au (0.1 ppm). Py2a is enriched in Co (43.1 ppm) and Ni (50.9 ppm), but depleted in As and Au. By contrast, Py2b is enriched in As (7894 ppm) and Au (0.5 ppm), but depleted in Co and Ni. Although, Py3 shows enrichment in Co (1319 ppm) and Ni (1783 ppm), it is usually accompanied with chalcopyrite and visible gold. Three generations of gold-associated pyrite indicate three stages of hydrothermal mineralization, and the variation of metals in pyrite suggest that the ore-forming materials were predominantly derived from felsic magma mixed with different proportion of mafic-volcanic host rocks. U-Pb dating on hydrothermal monazite from stage III constrains the mineralization age at 227 ± 7 Ma, which is coeval with the concealed granite porphyry (228 Ma). The δ 34 S values of the pyrites vary from +4.8‰ to +8.9‰, which are slightly higher than magmatic pyrite in porphyry (+4.2‰ to +5.6‰). We tentatively propose that the ore-forming materials are closely related to the granite porphyry and the evolved magmatic hydrothermal fluids.